2016
DOI: 10.1039/c6sm01186a
|View full text |Cite
|
Sign up to set email alerts
|

Membrane stiffness is modified by integral membrane proteins

Abstract: Large coarse-grained simulations show that integral membrane proteins alter the bending rigidity of lipid bilayers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
113
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(126 citation statements)
references
References 90 publications
3
113
0
Order By: Relevance
“…For bacteriorhodopsin, the bending modulus did not show any measurable dependence on protein concentration in the vesicles, but a significant reduction in bending modulus values was observed when Ca‐ATPase was added to giant unilamellar vesicles . Moreover, recent simulations have shown that integral membrane proteins can have diverse effects on membrane mechanics, either softening, neutral, or stiffening . None of these studies, however, have considered the effect of a large variety of proteins on the mechanics of membranes of complex lipid mixtures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For bacteriorhodopsin, the bending modulus did not show any measurable dependence on protein concentration in the vesicles, but a significant reduction in bending modulus values was observed when Ca‐ATPase was added to giant unilamellar vesicles . Moreover, recent simulations have shown that integral membrane proteins can have diverse effects on membrane mechanics, either softening, neutral, or stiffening . None of these studies, however, have considered the effect of a large variety of proteins on the mechanics of membranes of complex lipid mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…[8] Moreover, recent simulations have shown that integral membrane proteins can have diverse effects on membrane mechanics, either softening, neutral, or stiffening. [9] None of these studies, however, have considered the effect of a large variety of proteins on the mechanics of membranes of complex lipid mixtures.…”
mentioning
confidence: 99%
“…37 Recent simulations reconcile some of these results by reporting how integral membrane proteins can have diverse effects on membrane mechanics, either softening, neutral or stiffening. 38 Here, we use atomic force microscopy (AFM) nano-indentation for mechanical characterization of RBC EVs. We use quantitative image analysis and show that RBC EVs remain in a rather spherical shape upon adhesion to the sample surface.…”
Section: Introductionmentioning
confidence: 99%
“…Given that ganglioside head groups support strong cohesive interactions with invasive toxins, and tend to facilitate membrane reshaping due to their high intrinsic positive curvature, we next explored the interaction of OMVs with more complex models of host membranes. [36][37][38][39][40][41] Both OMVs were simulated with a pre-equilibrated, [32][33][34][35][36][37][38][39][40][41][42][43][44][45] multicomponent plasma membrane model composed of POPC (25%), POPE (25%) 1palmitoyl-2-oleoyl phosphatidyl serine, or POPS (7.5%), GM3 ganglioside (5%), sphingomyelin (7.5%), cholesterol (25%) and phosphatidylinositol 4,5-biphosphate, or PIP 2 (5%). Table 3 and Table 4 summarize the findings from these simulations, which are described in detail below.…”
Section: Omvs Interacting With Model Plasma Membranesmentioning
confidence: 99%